Modeling and simulation of 1-phase to 2-phase matrix converter motor drive - Boztas, Gullu; Sunter, Sedat; Aydogmus, Omur (Institute of Electrical and Electronics Engineers Inc., 2014)
In this study, a novel direct ac-ac converter which contains one more leg in addition to the well known two-leg direct ac-ac converter has been proposed. Therefore, two output phases with 90o phase shift between them are obtained to drive a two-phase induction motor. Firstly, two passive loads consisting of resistances and inductances in series have been connected between these two legs to validate the control algorithm and converter operation. Then, the main and auxiliary windings of the single-phase induction motor have been connected to the output phases as a load. A phase difference of 90o has been obtained between the windings to generate maximum torque without using any starting capacitor. Thus, the phase difference between the windings has been provided by the proposed modulation algorithm. Model of the proposed converter and its load has been obtained by MATLAB/Simulink and the results of the simulation have been given under various operating conditions. © 2014 IEEE.
16th International Power Electronics and Motion Control Conference and Exposition, PEMC 2014 -- 21 September 2014 through 24 September 2014 -- Antalya -- 109695
Keywords: Modeling; Simulation; Single-phase induction motor; Single-phase matrix converter